Metalloproteomic approach of mercury-binding proteins in liver and kidney tissues of Plagioscion squamosissimus (corvina) and Colossoma macropomum (tambaqui) from Amazon region: Possible identification of mercury contamination biomarkers - Bittarello, Alis Correia [UNESP]; Vieira, José Cavalcante Souza [UNESP]; Braga, Camila Pereira; da Cunha Bataglioli, Izabela [UNESP]; de Oliveira, Grasieli [UNESP]; Rocha, Leone Campos [UNESP]; Zara, Luiz Fabrício; Buzalaf, Marília Afonso Rabelo; de Oliveira, Lincoln Carlos Silva; Adamec, Jiri; de Magalhães Padilha, Pedro [UNESP] (Elsevier, 2020)
Fish is an important source of protein, vitamins, and minerals. However, this food is also a major source of human exposure to toxic contaminants such as mercury. Thus, this paper aimed to evaluate mercury-binding proteins for possible application as biomarkers of mercury contamination in hepatic and renal tissues of Plagioscion squamosissimus (carnivorous fish) and Colossoma macropomum (omnivorous fish) from the Amazon region using metalloproteomic approach. The proteome of hepatic and renal tissues of fish species was separated by two-dimensional polyacrylamide gel electrophoresis (2D-PAGE), and the mercury concentrations in protein spots were determined by graphite furnace atomic absorption spectrometry (GFAAS). Finally, the protein spots associated to mercury were characterized by electrospray ionization mass spectrometry (ESI-MS/MS). The activity of antioxidant enzymes (SOD, CAT, GPx, and GST) and lipid peroxidation (LPO) were also determined. The results showed that the highest concentrations of mercury were found in the carnivorous species (P. squamosissimus) and that the accumulation pattern of this metal was higher in hepatic tissues than in renal tissues for both species. A tendency was observed for greater enzymatic activity in the hepatic and renal tissues of P. squamosissimus, the species with the highest concentration of mercury. Only GPx activity in the kidney and GST in the liver were lower for the P. squamosissimus species, and this finding can be explained by the interaction of mercury with these enzymes. The data obtained by ESI-MS/MS allowed for the characterization of the protein spots associated to mercury, revealing proteins involved in energy metabolism, biomolecules transport, protein synthesis and degradation, cell differentiation, gene regulation, and the antioxidant system. The results obtained in the present study can contribute to understanding the physiological processes underlying mercury toxicity and have provided new perspectives on possible candidates for mercury contamination biomarkers in fish.
Keywords: Mercury and oxidative stress; Mercury in fish tissues; Mercury-binding protein; Metalloproteomic